DINAMIKA SISTEM PENDIDIKAN NASIONAL: ANALISIS FILOSOFIS, SOSIOLOGIS, PSIKOLOGIS, DAN YURIDIS DALAM MANAJEMEN PENDIDIKAN - Sutrisno; Solikah, Binti; Agus Tinus (STKIP Subang, 2026)
This study aims to analyze the dynamics of the national education system through philosophical, sociological, psychological, and juridical perspectives within the framework of educational management. This research employs a qualitative approach with a library research method, utilizing data from scientific journals, academic books, and official policy documents related to the national education system. Data were analyzed using content analysis techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that the national education system is a complex and dynamic system influenced by interconnected educational foundations. Philosophical foundations provide direction and values, sociological foundations reflect social contexts, psychological foundations emphasize learners’ characteristics, and juridical foundations ensure regulatory compliance. Furthermore, the application of systems theory in educational management enables a holistic understanding of the relationships between input, process, output, and outcome. The integration of these perspectives is essential in creating an effective, adaptive, and sustainable education system. Therefore, educational management must be conducted comprehensively by integrating these dimensions to improve the quality of national education.